Immersive experiences in dark Tourism: augmented reality application in Ibarra - Ortiz Cumbal, Dennis Victoria; Cedeño Vinces, Kimberly Lizeth; Ruiz Erazo, Victoria Geovanna (Tierra Infinita, 2024)
The city of Ibarra reveals a promising potential for the development of tourist attractions, especially in the field of “dark tourism” and even more so by taking advantage of augmented reality technology. This opportunity is presented as a clear path towards the incorporation of such technology, covering not only cemeteries, but also homes with stories of spirits, legends and places related to paranormal experiences. The application of this technology is seen as a competitive factor both locally and nationally, which encompasses significant benefits for the entire community. Therefore, the present study proposes the conceptualization of a tourist route that integrates the paranormal and the technological innovation. For its development, qualitative and quantitative research approaches were employed, integrating analytical, synthetic, and deductive methods. Likewise, and end exhaustive bibliographic analysis, field and comparative research were carried out, making use of techniques such as observation, comparative tables, and surveys. The sample, composed of 64 tourist and residents of Ibarra, was a non-probabilistically for convenience. The results obtained expose detailed information on the degree of interest in dark tourism and augmented reality by the participants. Based in these findings, the creation of a prototype of a tourist route in Ibarra that integrates augmented reality and dark tourism is proposed, with the aim of attracting both tourists and residents, providing them with avant-garde and unusual tourist experiences.